NK Cells Contribute to Protective Memory T Cell Mediated Immunity to Chlamydia muridarum Infection - Wang, Hong; Li, Jing; Dong, Xiaojing; Zhou, Xaoqing; Zhao, Lei; Wang, Xiao; Rashu, Rasheduzzaman; Zhao, Weiming; Yang, Xi (Frontiers in Cellular and Infection Microbiology, 2020)
We previously reported that NK cells can promote type 1 T cell immune response that is essential for protection to a primary infection of Chlamydia muridarum. In this study, we have investigated the contribution of NK cells to memory T cells response associated immunity during chlamydial infection. We have found that NK cell depletion led to impaired production of IFN-γ by memory T cells upon re-stimulation with chlamydial antigens in vitro. Mice with depleted NK cells also exhibited reduced type 1 of T cell recall responses, with increased production of IL-4 from CD4+ T cells and a lower level of Chlamydia-specific IgG2a titers compared to control mice. In addition, Treg response was significantly increased in mice with NK cell depletion. Moreover, NK cell-depleted mice showed an increased bacterial loads and more severe inflammatory pathological changes than control mice. These findings indicate that NK cells contribute to protective T cell memory associated immunity to chlamydial re-infection through modulating the cytokine pattern of T cell and inhibition of Treg responses.